Problematizing leniency and panopticism - Petković, Danijela (Primerjalna književnost, 2018)
The paper discusses Joseph O' Connor's 2002 novel, Star of the Sea, and Sarah Waters' Affinity (1999), in terms of their shared depiction of the Victorian prison, contra Foucault, as the space of corporal punishment and torture. The novels and the paper contextualize Victorian prisons within the nineteenth century discourses of progress, correction and reform, while simultaneously emphasizing the punitive and sadistic aspects of these fast-growing institutions. Detailing the organization of space; the architecture of surveillance; and the interpersonal power dynamics between the guards and the inmates, Star of the Sea and Affinity undermine the supposed humaneness of a prison sentence as a non-corporal, reformed and reforming, type of punishment - thus refusing, just like Discipline and Punish, to "sing the praises that the law needs". Yet O'Connor's and Waters' novels also problematize Foucault's notion of prison as the model of disciplinary society. Supported by contemporary research on Victorian penology and imprisonment and the nineteenth-century reports on prison life, the two novels demonstrate that it is (the threat of) the prison's monopolized violence rather than the internalized consciousness of surveillance that regulates both convicts and citizens.
Keywords: angleška književnost; irska književnost; kaznovanje; književnost in družba; O'Connor, Joseph; telesna kazen; telo; viktorijanska doba; Waters, Sarah; zapor